2020
DOI: 10.3390/ijms21051755
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of DUB Genes in Ovarian Cells Treated with Di-2-Ethylhexyl Phthalate

Abstract: Premature ovarian failure (POF) is defined as loss of ovarian function in women less than 40 years of age. The causes of POF are diverse and include environmental factors. Di-2-ethylhexyl phthalate (DEHP) is one factor that may cause POF. The ubiquitin-proteasome system maintains intracellular balance by promoting or inhibiting protein degradation. To investigate the differential expressions of deubiquitinating enzyme (DUB) genes in patients with POF, we developed two in vitro POF models by treating A2780 or O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Similarly, VEGFA plays an important role in ovarian morphogenesis (McFee & Cupp, 2013). Lee, Park, et al (2020) showed that USP49 was one of the potential biomarkers of premature ovarian failure. Gao et al (2021) illustrated that USP25 affected granulosa cell apoptosis by regulating the PI3K/AKT signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, VEGFA plays an important role in ovarian morphogenesis (McFee & Cupp, 2013). Lee, Park, et al (2020) showed that USP49 was one of the potential biomarkers of premature ovarian failure. Gao et al (2021) illustrated that USP25 affected granulosa cell apoptosis by regulating the PI3K/AKT signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…tant role in ovarian morphogenesis(McFee & Cupp, 2013) Lee, Park, et al (2020). showed that USP49 was one of the potential biomarkers of premature ovarian failure Gao et al (2021).…”
mentioning
confidence: 99%